Food truck fever: a spatio-political analysis of food truck activity in Kansas City, Missouri - Petersen, Deanne (Kansas State University, 2014)
Planning researchers and professionals have recently noted the social, economic, and cultural benefits food truck activity can provide within a community. As a result, the proliferation of food truck activity has challenged planners to reconsider the role of streets and urban spaces. Food trucks have the potential to enliven the urban landscape and enrich the quality of public life by serving as revitalization catalysts in urban spaces. While food trucks have become an increasingly visible aspect of street life, few jurisdictions have determined an effective manner to regulate and promote food truck activity. The study recommends how cities can improve current food truck policies in order to enable the revitalization of urban spaces through food truck activity. Using Kansas City, Missouri as a study area, the primary question was explored through three secondary inquires and their related methods. First, a GIS-based spatial analysis identified the spatio-temporal characteristics of food truck locations via social media data mining processes. Second, a survey of food truck vendors and interviews with city staff highlighted stakeholder conflicts that pose barriers to food truck activity. Third, a policy review in key cities and the development of a policy framework helped determine appropriate policy guidelines that allow food trucks to operate effectively in a city. The cumulative findings of the study informed food truck policy guidelines for Kansas City, Missouri. The policy framework also provides a structure for cities to utilize in order to analyze their own regulations. Sixteen significant policy areas are included in the framework, with the policy areas falling into one of three categories: permitting and enforcement, streets and spaces, or public health and safety. Appropriate policies that balance the needs of stakeholders allow food trucks to operate effectively, thus allowing cities to capitalize on the urban revitalization effects and other benefits that food truck activity provides within urban spaces.
Keywords: Food truck; Planning; Policy; Kansas City; Area Planning and Development (0341); Public Policy and Social Welfare (0630); Urban Planning (0999)